2010
DOI: 10.1002/jhm.609
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional analysis of hospitalist prevalence and quality of care in California

Abstract: BACKGROUND:Hospital leaders usually provide financial support to hospitalists groups, often with an expectation of improved performance on publicly reported quality metrics. Whether the presence of hospitalists is associated with differences in hospital‐level performance is unknown.OBJECTIVE:Assess the relationship between hospitalist prevalence and quality performance.DESIGN:Cross‐sectional study.PARTICIPANTS:A total of 208 California hospitals participating in a voluntary reporting initiative.INTERVENTION:Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Seventy-seven articles met these initial inclusion criteria. Upon examination of the full papers, five of these articles were excluded because control patients received significant cross-over of care from the hospitalist physicians [30-34], and three other articles were excluded because healthcare quality was examined among hospitals with and without hospitalists, regardless of whether the sampled patients actually received direct hospitalist care [35-37]. Two papers were excluded because the intervention involved the addition of a hospitalist medical director, as opposed to a hospitalist physician, providing direct inpatient care [38,39], and one paper was excluded because the intervention did not meet a widely accepted definition of a hospitalist program in that no physician spent more than 25% of his or her professional time working as an inpatient specialist [40].…”
Section: Methodsmentioning
confidence: 99%
“…Seventy-seven articles met these initial inclusion criteria. Upon examination of the full papers, five of these articles were excluded because control patients received significant cross-over of care from the hospitalist physicians [30-34], and three other articles were excluded because healthcare quality was examined among hospitals with and without hospitalists, regardless of whether the sampled patients actually received direct hospitalist care [35-37]. Two papers were excluded because the intervention involved the addition of a hospitalist medical director, as opposed to a hospitalist physician, providing direct inpatient care [38,39], and one paper was excluded because the intervention did not meet a widely accepted definition of a hospitalist program in that no physician spent more than 25% of his or her professional time working as an inpatient specialist [40].…”
Section: Methodsmentioning
confidence: 99%
“…Our survey was adapted from the survey developed by Vasilevskis et al [6]. The entire survey can be found in the Appendix.…”
Section: Methodsmentioning
confidence: 99%
“…2) Approximately what percent of all medical patients in your hospital are admitted by hospitalists? The latter question was intended as an approximation of the intensity of hospitalist use, and has been used in prior studies [6,14]. A more direct measure was not feasible given the complexity of obtaining admission data for such a large and diverse set of hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, later multiple studies regarding internal medicine hospitalists have shown improvement in care quality for pneumonia, myocardial infarction, and hospital stay, and readmission rates. 3,4 With these quality and known workplace improvements, the utilization of hospitalists now covers a quarter of all Medicare admissions and has increased by 25% from 2009 to 2011. 5 The obstetric hospitalist movement initially developed in a similar means with limited early data, but is now progressing toward measurement of its effects on patients.…”
mentioning
confidence: 98%